Spinel-type lithium manganese oxide, its manufacturing method and its use
By integrating lithium silicate into spinel-type lithium manganate, the material's high-temperature charge and discharge characteristics are improved, addressing the stability issues and enhancing lithium-ion secondary battery performance.
Patent Information
- Application Number
- JP2021050758
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-24
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-03-24
AI Technical Summary
Spinel-type lithium manganate exhibits poor high-temperature stability, particularly in charge and discharge characteristics with carbon counter electrodes, necessitating improved performance for lithium-ion secondary batteries.
Incorporating lithium silicate into spinel-type lithium manganate, with a chemical formula Li1+X Mn2-X-Y MgY O4, where 0.05≦X≦0.25 and 0.01≦Y≦0.10, to enhance high-temperature charge and discharge characteristics.
The lithium silicate modification significantly improves the charge and discharge characteristics of spinel-type lithium manganate at high temperatures, particularly with carbon counter electrodes, leading to enhanced performance in lithium-ion secondary batteries.
Smart Images

Figure 0007661739000003 
Figure 0007661739000004 
Figure 0007661739000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a spinel-type lithium manganese oxide, a manufacturing method thereof, and uses thereof. More specifically, the present invention relates to a spinel-type lithium manganese oxide having lithium silicate supported on its surface, a manufacturing method thereof, and a lithium ion secondary battery using the same in an electrode. [Background technology]
[0002] Lithium-ion secondary batteries have a higher energy density than other storage batteries, and are therefore widely used as storage batteries for mobile devices. Recently, research has been conducted to further improve their performance, including their application to large-scale, large-capacity, and high-output applications such as stationary and automotive use.
[0003] The positive electrode materials of lithium-ion secondary batteries currently in use are mainly cobalt-based materials (LiCoO2) for small consumer batteries such as mobile phones, and nickel-based materials (LiNi 0.8 Co 0.15 Al 0.05 O2) and nickel-cobalt-manganese ternary materials (LiNi 0.5 Co 0.2 Mn 0.3 However, cobalt-based and nickel-based materials are not abundant in resources, are expensive, and do not have high output characteristics.
[0004] On the other hand, spinel-type lithium manganese oxide, a manganese-based material, is one of the materials suitable for large batteries and applications requiring high output, because the raw material manganese is abundant and inexpensive, and it also has excellent output characteristics and safety.
[0005] However, spinel-type lithium manganese oxide has problems with high-temperature stability, that is, with its charge / discharge characteristics at high temperatures, particularly with its carbon counter electrode charge / discharge characteristics and storage characteristics, and a solution to this problem has been desired. For example, Non-Patent Document 1 proposes a nickel-cobalt-manganese ternary material containing a lithium-based oxide such as lithium silicate as a surface modifier. There is room for improvement in the charge / discharge characteristics of the carbon counter electrode by adding lithium silicate to spinel-type lithium manganese oxide. [Prior art documents] [Non-patent literature]
[0006] [Non-Patent Document 1] Journal of Power Sources 343 (2017) 345-353 Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a spinel-type lithium manganese oxide having excellent charge-discharge characteristics under a load at high temperatures, in particular, a spinel-type lithium manganese oxide having excellent charge-discharge characteristics by using carbon for the negative electrode, and further to provide a lithium ion secondary battery using the spinel-type lithium manganese oxide for the positive electrode. [Means for solving the problem]
[0008] As a result of extensive research into spinel-type lithium manganese oxide, the present inventors have found that the present invention, which is summarized below, can achieve the above-mentioned object. That is, the present invention relates to a lithium manganese oxide that contains lithium silicate and has the chemical formula Li 1+X Mn 2-X-Y Mg Y The present invention relates to a spinel-type lithium manganese oxide represented by the formula (X, Y, and Y) of 0.05≦X≦0.25, 0.01≦Y≦0.10, a method for producing the same, and uses thereof. Effect of the Invention
[0009] When the spinel-type lithium manganese oxide of the present invention is used as a positive electrode material for a lithium ion secondary battery, it has superior charge-discharge characteristics at high temperatures compared to conventional materials. In particular, it is possible to provide a lithium ion secondary battery having excellent charge-discharge characteristics when used with a carbon counter electrode. [Brief description of the drawings]
[0010] [Figure 1] 1 is a SEM-EDX image of the lithium silicate-containing spinel-type lithium manganate particles obtained in Example 1. [Diagram 2] 1 is a SEM-EDX image of the lithium silicate-containing spinel-type lithium manganese oxide particles obtained in Example 2. [Diagram 3] 1 is a SEM-EDX image of the lithium silicate-containing spinel-type lithium manganate particles obtained in Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below.
[0012] The spinel-type lithium manganate of the present invention contains lithium silicate. By containing lithium silicate, when the spinel-type lithium manganate of the present invention is used as a positive electrode active material of a lithium ion secondary battery, it is possible to obtain excellent charge and discharge characteristics at high temperatures. Examples of lithium silicate include lithium silicates such as Li2SiO3, Li4SiO4, Li2Si2O5, and Li2Si3O7, but Li2SiO3 is preferred because it is easy to synthesize. Here, when the spinel-type lithium manganate contains lithium silicate, for example, lithium silicate exists as fine particles or exists as a film on the surface of the spinel-type lithium manganate. There is no particular restriction on the properties of the lithium silicate, and examples include crystalline ones, crystalline and porous ones, crystalline and dense ones, amorphous ones, amorphous and porous ones, and amorphous and dense ones, but are not limited thereto.
[0013] The silicon / manganese molar ratio is preferably 0.008 or more and 0.03 or less. By having a silicon / manganese molar ratio of 0.008 or more and 0.03 or less, when used as a positive electrode active material for a lithium ion secondary battery, a reaction occurs in which lithium silicate inhibits a reaction caused by hydrogen fluoride contained in a small amount in the electrolyte of the lithium ion secondary battery. As a result, manganese elution caused by the reaction between hydrogen fluoride and spinel-type lithium manganate is suppressed, making it possible to suppress a capacity decrease during charging and discharging at high temperatures. The silicon / manganese molar ratio is more preferably 0.009 or more and 0.03 or less.
[0014] The lithium silicate contained in the present invention is present only on the surface of the spinel-type lithium manganate particles. The average particle size of the lithium silicate is preferably 0.3 μm or more and 1 μm or less.
[0015] The spinel-type lithium manganese oxide of the present invention has the chemical formula Li 1+X Mn 2-X-Y Mg Y O4 (wherein 0.05≦X≦0.25, 0.01≦Y≦0.10 are satisfied). If the value of X is less than 0.05, the capacity is likely to decrease during charging and discharging at high temperatures, and if it exceeds 0.25, sufficient charging and discharging capacity cannot be obtained. If the value of Y is less than 0.01, the capacity is likely to decrease during charging and discharging at high temperatures, and if it exceeds 0.10, sufficient charging and discharging capacity cannot be obtained. X and Y of the spinel-type lithium manganate can be determined by composition analysis. Examples of the method include inductively coupled plasma emission spectrometry and atomic absorption spectrometry.
[0016] The spinel-type lithium manganese oxide of the present invention has a BET specific surface area of 0.1 m 2 / g or more 1.2m 2 / g or less. The BET specific surface area is preferably 0.1 m 2 / g or more 1.2m 2 / g or less, it is possible to obtain excellent charge / discharge characteristics at high temperatures and excellent output characteristics when used as a positive electrode active material for a lithium ion secondary battery. 2 / g or more 1.0m 2 / g or less is preferable, and 0.3m 2 / g or more 0.8m 2 / g or less is more preferable.
[0017] In the spinel-type lithium manganate of the present invention, the average particle diameter of the secondary particles is preferably 4 μm or more and 12 μm or less. By having the average particle diameter of the secondary particles be 4 μm or more and 12 μm or less, when used as a positive electrode active material of a lithium ion secondary battery, it is possible to obtain excellent output characteristics and to increase the filling property of the positive electrode mixture. The average particle diameter of the secondary particles is preferably 5 μm or more and 10 μm or less.
[0018] In order to prevent capacity reduction due to impurities, the spinel-type lithium manganate of the present invention preferably has an SO4 content of 0.3 wt% or more and 1.0 wt% or less, and more preferably 0.4 wt% or more and less than 0.8 wt%.
[0019] In the spinel-type lithium manganese oxide of the present invention, the Na content is preferably 500 wtppm or less, and more preferably 300 wtppm or less, in order to prevent a decrease in capacity, as described above.
[0020] Next, a method for producing the spinel-type lithium manganese oxide of the present invention will be described.
[0021] The spinel-type lithium manganate of the present invention can be obtained by mixing a manganese raw material, a lithium raw material, and a silicate raw material in predetermined amounts, firing the mixture at 850°C to 930°C in air or in a high-oxygen atmosphere (including a pure oxygen atmosphere), and crushing the mixture.
[0022] There is no particular limitation on the manganese raw material, but crystallized Mn3O4, electrolytic MnO2, or Mn2O3 obtained by calcining crystallized Mn3O4 or electrolytic MnO2 are preferred, since they can increase the concentration of spinel-type lithium manganese oxide.
[0023] The lithium raw material is not particularly limited, and examples thereof include lithium carbonate, lithium hydroxide, lithium nitrate, lithium chloride, lithium iodide, and lithium oxalate, but are not limited thereto.
[0024] The lithium silicate raw material is not particularly limited, and examples thereof include silica particles SiO2, SiO2 particle precursors such as tetraethoxysilane Si(OC2H5)4 and tetramethoxysilane Si(OCH3)4, and other silicon metal alkoxides, lithium silicate, etc. Examples of lithium silicate include Li2SiO3 and Li4SiO4.
[0025] The amount of manganese and lithium materials to be mixed is determined by the chemical formula Li 1+X Mn 2-X-Y Mg Y The amount of the silicic acid raw material is an amount for obtaining a spinel-type lithium manganese oxide having a formula of 0.05≦X≦0, 25, 0.01≦Y≦0.10. The amount of the silicic acid raw material is an amount for obtaining a Si / Mn molar ratio of 0.008 to 0.03.
[0026] Examples of the method for mixing the manganese raw material, the lithium raw material, and the lithium silicate raw material include dry mixing, wet mixing, etc. In the case of wet mixing, a method is exemplified in which the lithium silicate raw material is dispersed or dissolved in water as a solvent, and then added to the manganese raw material and the lithium raw material.
[0027] The calcination for obtaining the spinel-type lithium manganate of the present invention is carried out in air or in a high-concentration oxygen atmosphere (including a pure oxygen atmosphere), i.e., in an oxygen atmosphere with an oxygen content of 18 vol% to 100 vol%, at 850°C to 930°C. At temperatures lower than 850°C, the BET specific surface area of the spinel-type lithium manganate tends to increase, while at temperatures exceeding 930°C, the oxygen deficiency of the spinel-type lithium manganate increases, and as a result, the charge-discharge cycle characteristics tend to decrease when used as a positive electrode active material for a lithium secondary battery. The calcination is preferably carried out at 900°C to 930°C.
[0028] Since the secondary particles of spinel-type lithium manganate tend to agglomerate during firing, the material is crushed to obtain the desired particle size. The crushing method is preferably by shear force to suppress the generation of fine powder and the increase in the BET specific surface area.
[0029] After crushing the spinel-type lithium manganese oxide, it is preferable to pass it through a sieve to remove coarse particles that exceed the thickness of the positive electrode. The sieve preferably has an opening of 100 μm or less, more preferably 50 μm or less.
[0030] By using the spinel-type lithium manganese oxide containing the lithium silicate of the present invention in the positive electrode of a lithium ion secondary battery, it becomes possible to configure a lithium ion secondary battery that has excellent charge / discharge cycle characteristics at high temperatures and excellent output characteristics, which were not previously obtainable.
[0031] The structure of the lithium ion secondary battery other than the positive electrode is not particularly limited. However, the negative electrode is preferably made of a material that absorbs and releases Li, such as a carbon-based material, a tin oxide-based material, or Li4Ti5O 12 , SiO, and materials that form an alloy with Li. Examples of materials that form an alloy with Li include silicon-based materials and aluminum-based materials. Examples of electrolytes include organic electrolytic solutions in which Li salts and various additives are dissolved in an organic solvent, Li-ion conductive solid electrolytes, and combinations of these. EXAMPLES
[0032] The present invention will be described with reference to specific examples, but the present invention is not limited to these examples.
[0033] <Battery performance test> 25 mg of the spinel-type lithium manganate obtained in each Example was mixed with 12.5 mg of a conductive binder (product name: TAB-2, manufactured by Hosen) in an agate mortar. This mixture was applied to a SUS mesh (SUS316) with a diameter of 16 mm at 2 ton / cm 2 The mixture was uniaxially pressed at 400° C. to prepare a pellet having a disk shape, which was then dried at 150° C. for 2 hours under reduced pressure to prepare a positive electrode.
[0034] A spherulitic graphite sheet (Hosen TSG-A1, nominal capacity 1.6 mAh / cm) was used as the negative electrode. 2 ) is punched out to a diameter of 16.156 mm. Then, it is subjected to 3 ton / cm 2 The specimens were uniaxially pressed at 1000 rpm.
[0035] LiPF6 is added at 1 mol / dm in a solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:2. 3 The dissolved material was used as the electrolyte, a polyethylene sheet (product name: Celgard, manufactured by Polypore) was used as the separator, and a battery was fabricated using a CR2032 coin cell as the cell.
[0036] Using the fabricated battery, the current density was 0.14 mA / cm at a cell voltage between 4.25 V and 3.0 V at 24°C. 2 The battery was then subjected to one cycle of constant current / constant voltage charge / constant current discharge at 24°C, with the cell voltage between 4.25 V and 3.0 V, and a current density of 0.28 mA / cm 2A constant current constant voltage charge - constant current discharge was performed for one cycle, and the discharge capacity was taken as the battery capacity. Next, at 60 °C, a constant current constant voltage charge - constant current discharge was performed 50 cycles between a cell voltage of 4.25 V and 3.0 V at a current density of the 1 - hour discharge rate with respect to the battery capacity, and the charge - discharge cycle characteristics of the carbon counter electrode were determined from the ratio of the discharge capacity of the 50th cycle to that of the 1st cycle. The end condition of the constant voltage charge was set at the point when the charging current decayed to 1 / 10 of that during the constant voltage charge.
[0037] <Measurement of composition analysis, SO4 content, Na content, and Si content> For the composition, SO4 content, and Na content of the spinel - type lithium manganate obtained in the examples and comparative examples, after dissolving the spinel - type lithium manganate in a hydrochloric acid - hydrogen peroxide mixed aqueous solution, it was analyzed with an inductively coupled plasma optical emission spectrometer (trade name: ICP - AES, manufactured by PerkinElmer Japan). Also, the Si content was analyzed using the above - mentioned apparatus for the sample dissolved in a hydrochloric acid - hydrogen peroxide - hydrofluoric acid mixed aqueous solution.
[0038] <Measurement of BET specific surface area> 0.5 g of the sample was placed in a glass cell for BET specific surface area measurement, and dehydration treatment was performed at 150 °C for at least 20 minutes under a nitrogen stream to remove the moisture adhering to the powder particles.
[0039] The treated sample was measured for BET specific surface area by the one - point method using a BET measuring apparatus (trade name: MICROMETRITICS DeSorbIII, manufactured by Shimadzu Corporation) with a mixed gas of 30% nitrogen - 70% helium as the adsorption gas.
[0040] <Average particle diameter of secondary particles of spinel - type lithium manganate> Using a particle size distribution measuring apparatus (trade name: MT3000II series, manufactured by MicrotracBEL), the average particle diameter (D 50 ) of the secondary particles of spinel - type lithium manganate was measured.
[0041] <XRD measurement> Regarding the spinel-type lithium manganate obtained in the examples and comparative examples, the measurement of the half-value width by XRD was performed using a powder XRD measuring device (trade name: Ultima IV, manufactured by Rigaku). The measurement conditions were as follows.
[0042] · Target: Cu · Output: 1.6 kW (40 mA - 40 kV) · Filter: Kβ filter · Divergence slit: 1 · Divergence vertical limiting slit: 10 mm · Scattering slit: Open · Receiving slit: Open · Scanning mode: Continuous · Scan speed: 4.000° / min · Sampling width: 0.04° (2θ / θ) · Integration times: 1 time · Measurement range: 10 - 90° (2θ / θ) The obtained XRD data of the spinel-type lithium manganate were analyzed using the analysis software (PDXL2) attached to the powder X-ray diffractometer.
[0043] <Measurement of particle surface SEM-EDX image> Using a scanning electron microscope (SEM, trade name: JSM-IT500, manufactured by JEOL Ltd.) / energy dispersive spectrometer (EDS, trade name: EX-74600U4L2Q, manufactured by JEOL Ltd.), the distributions of Mn and Si were measured at an acceleration voltage of 15 kV.
[0044] <Composition analysis by ICP> The composition, SO4 content, and Na content of the spinel-type lithium manganate obtained in the examples were analyzed using an inductively coupled plasma atomic emission spectrometer (trade name: ICP-AES, manufactured by PerkinElmer Japan) after heating and dissolving the spinel-type lithium manganate in a hydrochloric acid-hydrogen peroxide mixed aqueous solution.
[0045] Also, Si was analyzed by ICP-AES after heating and dissolving the spinel-type lithium manganate in a hydrochloric acid-hydrogen peroxide mixed aqueous solution and then adding hydrofluoric acid.
[0046] Example 1 The pure water at 60°C was stirred while air was blown into it. A 2 mol / L manganese sulfate aqueous solution and a 20 wt% sodium hydroxide aqueous solution were continuously added to the pure water while maintaining the oxidation-reduction potential of the pure water constant at 100 mV based on the hydrogen electrode standard. The resulting slurry was then filtered, washed, and dried to obtain Mn3O4 with an average particle size of 3.8 μm.
[0047] 0.57mL of a solution in which 10.0g of colloidal silica (trade name: LUDOX TM-50) was diluted to 10wt% was added to 10g of the obtained Mn3O4, and 5g of the mixture was dried at 120°C for 6 hours, mixed with 1.4g of lithium carbonate Li2CO3 and 0.11g of magnesium hydroxide Mg(OH)2 (manufactured by Wako Pure Chemical Industries, average particle size 0.07μm). This mixture was fired at 900°C for 6 hours in a box-type firing furnace while circulating air at a rate of 5L / min, and then cooled to room temperature. The heating rate was 100°C / hr, and the cooling rate was 20°C / hr from 900°C to 600°C, and 100°C / hr from 600°C to room temperature. The obtained lithium silicate-containing spinel-type lithium manganese oxide was crushed with an ultra-high speed crusher (rotary crusher, manufactured by Sansho Industry Co., Ltd.), and then passed through a sieve with an opening of 32 μm to obtain lithium silicate-containing spinel-type lithium manganese oxide. The composition of the obtained lithium silicate-containing spinel-type lithium manganese oxide was Li 1.12 Mn 1.85 Mg 0.03 The result was O4. XRD measurement also showed that the lithium silicate-containing spinel-type lithium manganese oxide was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 70-0330 (Li2SiO3). The silicon / manganese molar ratio, BET specific surface area, average particle size, Na content, and SO4 content (hereafter referred to as "measurement results") are shown in Table 1. The battery performance evaluation is shown in Table 2. An SEM-EDX image of the particle surface is shown in Figure 1.
[0048] [Table 1]
[0049] [Table 2] Example 2 A lithium silicate-containing spinel-type lithium manganate was obtained in the same manner as in Example 1, except that the amount of colloidal silica added was 1.14 g.
[0050] The composition of the obtained lithium manganese spinel oxide was Li 1.13 Mn 1.84 Mg 0.03 The phase of the material was O4. XRD measurement also showed that it was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 70-0330 (Li2SiO3). The measurement results are shown in Table 1, and the battery performance evaluation is shown in Table 2. The SEM-EDX image of the particle surface is shown in Figure 2.
[0051] Example 3 A lithium silicate-containing spinel-type lithium manganate was obtained in the same manner as in Example 1, except that the amount of colloidal silica added was 2.27 g.
[0052] The composition of the obtained lithium manganese spinel oxide was Li 1.20 Mn 1.85 Mg 0.03 The result was a mixture of JCPDS No. 35-782 (LiMn2O4) and No. 70-0330 (Li2SiO3) phases. The measurement results are shown in Table 1, and the battery performance evaluation is shown in Table 2. The SEM-EDX image of the particle surface is shown in Figure 3.
[0053] Comparative Example 1 After 3g of Mn3O4, 0.83g of Li2CO3, and 0.068g of Mg(OH)2 (manufactured by Wako Pure Chemical Industries, Ltd., average particle size 0.07μm) were mixed in a dry state, the mixture was fired, crushed, and classified in the same manner as in Example 1. The synthesized spinel-type lithium manganese oxide was a single phase of JCPDS No. 35-782 (LiMn2O4). The measurement results of the physical properties are shown in Table 1. The battery performance is also shown in Table 2. It is clear from Table 2 that the charge and discharge characteristics at high temperatures of Comparative Example 1 are inferior to those of the Examples.
[0054] Comparative Example 2 A lithium silicate-containing spinel-type lithium manganese oxide was obtained in the same manner as in Example 2, except that the amount of lithium carbonate Li2CO3 added was 1.08 g. The composition of the obtained spinel-type lithium manganese oxide was Li 0.85 Mn 2.12 Mg 0.03 The battery performance evaluation is shown in Table 2. It is clear from Table 2 that the charge / discharge characteristics at high temperatures in Comparative Example 2 are inferior to those in the Examples due to an insufficient Li composition.
[0055] Comparative Example 3 A lithium silicate-containing spinel-type lithium manganese oxide was obtained in the same manner as in Example 2, except that the amount of lithium carbonate Li2CO3 added was 1.79 g. The composition of the obtained spinel-type lithium manganese oxide was Li 1.41 Mn 1.56 Mg 0.03 The battery performance evaluation is shown in Table 2. From Table 2, it is clear that the charging capacity obtained in Comparative Example 3 is not sufficient compared to the Examples because of the excess Li composition. [Industrial Applicability]
[0056] The spinel-type lithium manganese oxide of the present invention has lithium silicate contained on the surface of the spinel-type lithium manganese oxide, and has a specific BET specific surface area and secondary particle size. Therefore, it has excellent charge / discharge characteristics at high temperatures, especially the charge / discharge characteristics of the carbon counter electrode. It can also be used as a positive electrode active material for lithium ion secondary batteries with excellent charge / discharge characteristics.
Claims
1. It contains lithium silicate and has the chemical formula Li 1+X Mn 2-X-Y Mg Y O 4 (wherein 0.05≦X≦0.25, 0.01≦Y≦0.10 are satisfied), A spinel-type lithium manganese oxide, characterized in that the lithium silicate is Li 2 SiO 3 .
2. The spinel-type lithium manganese oxide according to claim 1, characterized in that the silicon / manganese molar ratio is 0.008 or more and 0.03 or less.
3. BET specific surface area is 0.1m 2 / g or more 1.2m 2 3. The spinel-type lithium manganate according to claim 1, wherein the lithium manganese oxide has a molecular weight of 1.0 to 1.0 g / g or less.
4. 4. The spinel-type lithium manganate according to claim 1, wherein the average particle size of the secondary particles is 4 μm or more and 12 μm or less.
5. SO 4 The spinel-type lithium manganese oxide according to any one of claims 1 to 4, characterized in that the content of is 0.3 wt % or more and 1.0 wt % or less.
6. 6. The spinel-type lithium manganate according to claim 1, wherein the Na content is 500 wtppm or less.
7. The method for producing spinel-type lithium manganate according to any one of claims 1 to 6, characterized in that a manganese raw material, a lithium raw material, a magnesium raw material and a lithium silicate raw material are mixed, fired at 850°C or higher and 930°C or lower in air or in a high-concentration oxygen atmosphere (including a pure oxygen atmosphere), and then crushed.
8. An electrode comprising the spinel-type lithium manganese oxide according to any one of claims 1 to 6.
9. A lithium ion secondary battery, comprising the electrode according to claim 8 as a positive electrode thereof.
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery
JP1997245787A
Positive electrode for lithium secondary battery, and lithium secondary battery using it
JP2008293661A
Positive active material for nonaqueous electrolyte secondary battery, and the nonaqueous electrolyte secondary battery
JP2011216214A
Positive electrode active material particle powder for nonaqueous electrolyte secondary batteries, manufacturing method thereof, and nonaqueous electrolyte secondary battery
JP2016100174A
Positive electrode material for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery arranged by use thereof, and method for manufacturing positive electrode material for nonaqueous electrolyte secondary battery
JP2017188312A